Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
(-3√7)^2= 9*7=63 when you raise to the second power, -3 becomes 9
and √7 becomes 7
(3√11)^2=9*11=99
99+63=162
and √7 becomes 7
(3√11)^2=9*11=99
99+63=162
[tex](-3\sqrt{7})^{2} + (3\sqrt{11})^{2} \\(-3\sqrt{7})(-3\sqrt{7}) + (3\sqrt{11})(3\sqrt{11}) \\9\sqrt{49} + 9\sqrt{121} \\9(7) + 9(11) \\63 + 99 \\162[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.